Fenomena Cyberbullying di Media Sosial Instagram (Studi Deskriptif Tentang Kesehatan Mental Pada Generasi Z Usia 20-25 Tahun di Jakarta) - Azni Yeza Laora; Feri Sanjaya (Oratio Directa (Prodi Ilmu Komunikasi), 2021)
ABSTRACT Nowadays, the phenomenon of bullying has led to the emergence of a new trend known as cyberbullying. Cyberbullying is an act of insulting, humiliating, intimidating, and threatening someone by using electronic information or electronic documents. Cyberbullying is commonly found on social media especially on Instagram. Cyberbullying can happen to anybody, including Generation Z who is currently the main target with the most cyberbullying reports. This is because Generation Z grew up in the digital era, so they are familiar with technology and digital devices since childhood. Admit it or not, the technology that participates in the growth and development of Generation Z affects their personality. The forms of cyberbullying consist of; Harassment, Trickery, Denigration, Impersonation, and Flaming. The results of this study indicate that the cyberbullying committed and experienced by Generation Z can cause mental damage such as; depression, stress, paranoia, insecurity or loss of self-confidence, and temperamental. Jakarta is the center of most users of social media, especially Instagram. This study uses two theories, that is phenomenology and routine activities. The data collection technique was carried out by the author by observation, interviews, and literature study. Broadly, this study aims to provide knowledge about the importance of maintaining oral and written words on social media. The consequences of cyberbullying can lead to mental damage for those who experience it and those who do it. Keywords: Cyberbullying, Social Media Instagram, Mental Health, Generation Z,